DZIKIR DALAM TAFSIR SUFI IBNU ‘AJIBAH (al-Bahr al-Madid fi Tafsir al-Qur'an al-Madid) - Muhammad Ulil Abshor (Jurnal Ilmiah Ilmu Ushuluddin, 2020)
Abstract the importance of discussing Sufi interpretation is unfinished only on the meaning (inner) and exoteric meaning (outer). Al-Bahr al-Madid fi Tafsir al-Qur’an al-Majid by Ibn ‘Ajibah becomes the basic framework in explaining about dzikir (Remembering of God), dzikir intensely is not only in prayer (Sholat), but at the level of everytime, anytime and anywhere. However, the practice of worship outside of prayer is also called dzikr. The Dzikir of the main meaning of rememberring for the sake of purifying or glorifying Allah through His names (character). In essence dhikr has an orientation towards the social dimension, the life is full of tolerance, respect for each other is not concerned with self-arrogance. Growing on high wisdom values, especially in terms of morality, attitude, creative thinking so as to create a dignified life in the social, family and community. Dhikr is not only a mere utterance, but it involves positive social actions. This research method uses a comparison of interpretations and analyzes it to find the connection between dhikr that has an impact on social life. Sufistic approach and Hermeneutika Schleiermacher as binocular analysis. The results obtained that the dhikr are three things, oral, mind and heart. The three devices are manifested in the mental condition of a person who is able to ta'alluq (rests on his nature), takhallaq (berakhlaq with His attributes) and tahaqquq (to realize the manifestations of His attributes within himself). So it has an impact on the development of progressive life that is more meaningful in daily life.  Keywords: Dzikr, Sufi Tafsir, Social DimensionAbstrak pentingnya membahas tafsir sufi tidak selesai hanya pada makna (batin) dan makna eksoterik (zahir). Al-Bahr al-Madid fi Tafsir al-Qur’an al-Majid karya Ibnu ‘Ajibah menjadi kerangka dasar dalam menjelasakan dzikir, dzikir secara intens tidak hanya ada pada sholat, namun pada level everytime, anytime dan anywhere. Namun, praktik ibadah diluar sholat pun disebut pula dzikir. Dzikir makna zahirnya mengingat demi menyucikan atau mengagungkan Allah Swt melaui asma-asma-Nya. Pada hakikatnya dzikir memiliki orientasi mengarah pada dimensi sosial kemasyarakatan, hidup penuh toleran, saling menghargai tidak mementingkan arogansi diri. Tumbuh pada nilai hikmah yang tinggi utamanya dalam hal berakhlaq, bersikap, berfikir kreatif sehingga mewujudkan kehidupan yang bermartabat di lingkunan sosial, keluarga dan masyarakat. Dzikir tidak hanya sebagai ucapan belaka, akan tetapi menyangkut tindakan sosial yang positif. Metode penelitian ini menggunakan perbandingan tafsir dan menganalisisnya untuk menemukan keterkaitan dzikir yang berdampak dalam kehidupan sosial. Pendekatan sufistik dan Hermeneutika Schleiermacher sebagai teropong analisa. Hasil yang diperoleh bahwa dzikir itu tiga hal, lisan, akal dan hati. Ketiga perangkat tersebut mewujud pada kondisi mental seorang yang mampu ber-ta’aluq (sandaran pada sifat sifat-Nya), ber-takhallaq (berakhlaq dengan sifat sifat-Nya) dan ber-tahaqquq (merealisasikan wujud sifat sifat-Nya di dalam dirinya). Sehingga berdampak pada pengembangan progresifitas hidup yang lebih bermakna dalam kehidupan sehari hari. Keywords: Dzikir, Tafsir Sufi, Dimensi Sosial